Direct product of Intuitionistic fuzzy BG-Ideals in BG-Algebra (International Journal of Food and Nutritional Sciences, 2022)
In this paper, we introduced the concept of direct product of intuitionistic fuzzy BG-ideal in BG-algebra and investigate some of their basic properties.